Production of Biogas with Two-Stage Fermentation of Cow Dung-Palm Oil Mill Effluent - NH, Harmiwati; Supriadi, Eko; Rahmad, Dedy; Akbar, Addin; Khairati, Miftahul; Amrin, M. Zhafran Zharif; Adi, Tegar Trikora; Suhardito, Ibnu; Hidayat, Salsabila Alifia; Phuong, Nguyen Thi Thanh (Walisongo Journal of Chemistry, 2023)
In this research, biogas is produced from Palm Oil Mill Effluent (POME) by fermentation of cow dung using a stirred reactor and purified by various CO2 and H2S removal techniques. The variables in this study were: composition of cow dung (55%, 60%, 65%, 70%, 75%, 80% w/w), amino acid composition (0.5%, 1%, 1.5% w/w) and length of fermentation time (2, 6, 10, 14, 16 days). The fixed variables were stirring speed (100 rpm), temperature (30oC) and reactor volume (100 L). This research also investigated the effect of using a lime packed reactor on the purity of methane gas. From the results of first stage of fermentation, it was found that the optimum composition of cow dung-POME was at 60% and the fermentation time was 14 days. In the second stage of fermentation using optimum results at first stage compared to fermentation of cow dung without POME, the results of measuring the gas pressure produced in 60% cow dung-POME fermentation were 17.5 Psig greater than fermentation of cow dung without POME of 15 Psig.